2022
DOI: 10.3389/fncel.2022.919493
|View full text |Cite|
|
Sign up to set email alerts
|

GABA tonic currents and glial cells are altered during epileptogenesis in a mouse model of Dravet syndrome

Abstract: Dravet Syndrome (DS) is a rare autosomic encephalopathy with epilepsy linked to Nav1.1 channel mutations and defective GABAergic signaling. Effective therapies for this syndrome are lacking, urging a better comprehension of the mechanisms involved. In a recognized mouse model of DS, we studied GABA tonic current, a form of inhibition largely neglected in DS, in brain slices from developing mice before spontaneous seizures are reported. In neurons from the temporal cortex (TeCx) and CA1 region, GABA tonic curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Studies in experimental models of TLE reported that GABA released by reactive astrocytes from Bestrophin-1 channels strongly contributes to the compensatory shift of E/I balance in epileptic hippocampi. The tonic release of GABA from astrocytes is one of the key mechanisms by which astrocytes control epileptic seizures ( Crunelli et al, 2011 ; Muller et al, 2020 ; Goisis et al, 2022 ). By modulating tonic GABA release from astrocytes, it might be possible to target epileptic seizures and other neurological disorders ( Muller et al, 2020 ; Pandit et al, 2020 ).…”
Section: The Role Of Astrocytes In Structural/metabolic/infectious/im...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in experimental models of TLE reported that GABA released by reactive astrocytes from Bestrophin-1 channels strongly contributes to the compensatory shift of E/I balance in epileptic hippocampi. The tonic release of GABA from astrocytes is one of the key mechanisms by which astrocytes control epileptic seizures ( Crunelli et al, 2011 ; Muller et al, 2020 ; Goisis et al, 2022 ). By modulating tonic GABA release from astrocytes, it might be possible to target epileptic seizures and other neurological disorders ( Muller et al, 2020 ; Pandit et al, 2020 ).…”
Section: The Role Of Astrocytes In Structural/metabolic/infectious/im...mentioning
confidence: 99%
“…Dravet syndrome (DS)or myoclonic epilepsy in infancy (MEI) is a rare, genetic epileptic encephalopathy which is linked to de novo loss of function mutations of the SCNA1 gene encoding for the α subunit of Nav1.1 voltage-dependent sodium channels ( Claes et al, 2001 ). In experimental models of DS, during the development of seizures, changes in GABA A extrasynaptic receptor composition and GABA tonic currents have been recently shown to occur in parallel with an increase in microglia and astrocyte reactivity ( Satta et al, 2021 ; Goisis et al, 2022 ). Moreover, GAT-1 is expressed in the nerve endings of GABAergic interneurons and astrocytes.…”
Section: The Role Of Astrocytes In Genetic Generalized Epilepsiesmentioning
confidence: 99%
“…In SCN1A haplodeficient (-/+) mice, a Dravet syndrome model, one recent study reported increased GFAP expression and an increased number of Iba1-positive microglia in DG, implying increased reactivity of astrocytes and microglia (Goisis et al, 2022). Additionally, this study reported a reduction in tonic GABA current in CA1 pyramidal neurons, which needs further investigation due to its inconsistency with existing evidence showing the positive correlation between astrocytic reactivity and tonic GABA current (Goisis et al, 2022). In SCN2A-deficient mice, another study reported partially activated microglia, evidenced by increased cell bodies and reduced branches (Yang et al, 2023).…”
Section: Altered Hippocampal Glia-neuron Interactions In Asd Model An...mentioning
confidence: 99%
“…In recent work, by using a kindling model of epilepsy in the hippocampus, it was demonstrated that Zn 2+ decreases the antiseizure effects of ganaxolone by selectively blocking the extrasynaptic δ GABA A receptors (Chuang & Reddy, 2019). Also, it was reported that epilepsy associated with a mouse model of Dravet syndrome, involves a reduction of δ subunit mediated tonic currents in the entorhinal cortex and CA1 hippocampal neurons (Goisis et al., 2022). Previously, we have found that insulin (25–500 nM) increased inhibitory tonic currents mediated by α5 an δ subunit‐containing GABA A receptors in the prefrontal cortex (PFC).…”
Section: Introductionmentioning
confidence: 99%